2013
DOI: 10.1016/j.bone.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

3D image registration is critical to ensure accurate detection of longitudinal changes in trabecular bone density, microstructure, and stiffness measurements in rat tibiae by in vivo microcomputed tomography (μCT)

Abstract: In the recent decade, in vivo μCT scanners have become available to monitor temporal changes in rodent bone in response to diseases and treatments. We investigated short-term and long-term precision of in vivo μCT measurements of trabecular bone density, microstructure and stiffness of rat tibiae and tested whether they can be improved by 3D image registration. Rats in the short-term precision group underwent baseline and follow-up scans within the same day (n=15) and those in the long-term precision group wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…A recent study has demonstrated protective effects of PTH treatment against radiation damage [36], and our previous study showed high rates of bone formation in rats treated with PTH despite having received additional scans [10]; thus it is expected that scans on days 4 and 8 had no detrimental effects. As described in [10] and [34], rats were anesthetized (4.0/1.75% isoflurane), and the right leg of each rat was inserted into a custom holder to ensure minimal movement during the scan. A 4 mm region of the tibia distal to the proximal growth plate was scanned at 10.5 μm resulution, 55 keV energy, 145 μA intensity, 200 ms integration time, and 1000 projections, using a 0.5mm Al filter and a standard, manufacturer-provided beam-hardening correction algorithm, resulting in a total scan time of about 20 minutes and approximate radiation dose of 0.307 Gy per scan.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has demonstrated protective effects of PTH treatment against radiation damage [36], and our previous study showed high rates of bone formation in rats treated with PTH despite having received additional scans [10]; thus it is expected that scans on days 4 and 8 had no detrimental effects. As described in [10] and [34], rats were anesthetized (4.0/1.75% isoflurane), and the right leg of each rat was inserted into a custom holder to ensure minimal movement during the scan. A 4 mm region of the tibia distal to the proximal growth plate was scanned at 10.5 μm resulution, 55 keV energy, 145 μA intensity, 200 ms integration time, and 1000 projections, using a 0.5mm Al filter and a standard, manufacturer-provided beam-hardening correction algorithm, resulting in a total scan time of about 20 minutes and approximate radiation dose of 0.307 Gy per scan.…”
Section: Methodsmentioning
confidence: 99%
“…This was confirmed by greater increases in BV/TV, Tb.Th and decreases in BS/TV and slenderness in the explanted trabecular bone cores when exposed to LMHF loading compared to static and media flow only conditions. Image registration techniques were used to accurately determine changes in trabecular bone over the course of the experiment 37,52 . This finding agrees with the numerous other studies which display the positive effect of LMHF on trabecular bone 24,31,51,60 .…”
Section: Discussionmentioning
confidence: 99%
“…The scanner energy was 55 keV energy, intensity ¼ 142 lA, and integration time ¼ 200 ms. Rats were anesthetized and immobilized during the scans (4.0/1.75% isoflurane) using a customized foot holder to ensure minimal motion over the 20 min scan [28]. A two-dimensional (2D) scout view was used to select the scan region, and a total of 417 slices (corresponding to a 4.4 mm region) distal to the proximal tibial growth plate were acquired.…”
Section: Methods Of Approachmentioning
confidence: 99%
“…An open source software (National Library of Medicine Insight Segmentation and Registration Toolkit, USA) [32] was used to derive the transformation matrix between the image coordinates of baseline (F 1 ) and follow-up (F 2 ) lCT scans by landmarkinitialized, mutual-information-based optimization [33,34]. This optimization scheme has been described in detail in a previous publication [28]. In the traditional registration scheme, once a transformation matrix T between image coordinates of baseline (F 1 ) and follow-up (F 2 ) scans is determined, it will be applied to move the follow-up scan into (F 1 ).…”
Section: Precise Image Registration Of Trabecularmentioning
confidence: 99%
See 1 more Smart Citation